Risk Factor for Postoperative Pneumonia after Coronary Artery Bypass Grafting - Vita Karima Fadhilah; Chaerul Achmad; Rien Afrianti; Prayudi Santoso (Majalah Kardiologi Indonesia)
Background: Postoperative pneumonia (POP) is a common infectious complication of coronary artery bypass grafting (CABG), leading to significant morbidity, mortality, and increased healthcare costs. This study found that the prevalence of POP was nearly double that reported in previous studies, underscoring the urgent need to identify specific risk factors. These findings emphasize the importance of local data in refining preventive strategies and improving clinical outcomes in CABG patients.